Mangrove dolabrane‐type of diterpenes tagalsins suppresses tumor growth via ROS‐mediated apoptosis and ATM/ATR–Chk1/Chk2‐regulated cell cycle arrest. Issue 11 (30th June 2015) - Neumann, Jennifer; Yang, Yi; Köhler, Rebecca; Giaisi, Marco; Witzens‐Harig, Mathias; Liu, Dong; Krammer, Peter H.; Lin, Wenhan; Li‐Weber, Min
Abstract : Natural compounds are an important source for drug development. With an increasing cancer rate worldwide there is an urgent quest for new anti‐cancer drugs. In this study, we show that a group of dolabrane‐type of diterpenes, collectively named tagalsins, isolated from the Chinese mangrove genus Ceriops has potent cytotoxicity on a panel of hematologic cancer cells. Investigation of the molecular mechanisms by which tagalsins kill malignant cells revealed that it induces a ROS‐mediated damage of DNA. This event leads to apoptosis induction and blockage of cell cycle progression at S‐G2 phase via activation of the ATM/ATR—Chk1/Chk2 check point pathway. We further show that tagalsins suppress growth of human T‐cell leukemia xenografts in vivo . Tagalsins show only minor toxicity on healthy cells and are well tolerated by mice. Our study shows a therapeutic potential of tagalsins for the treatment of hematologic malignancies and a new source of anticancer drugs. Abstract : What's new? Mangroves of genus Ceriops, widespread and highly utilized in China, are of growing interest in anticancer drug development due to their production of potentially cytotoxic diterpenoids and triterpenoids. Here, a group dolabrane‐type diterpenes known as tagalsins isolated from the species C. tagal are shown to possess potent killing effects on cancer cells of hematologic origin. Cell death was associated with the production of reactive oxygen species and DNA damage. In vivo, tagalsins significantly delayed the development of human T‐cell leukemia in a murine xenograft model.